A MULTIFACETED FRAMEWORK FOR CRITICAL DIGITAL LITERACY IN TRANSFORMING HUMAN RESOURCES - Eka Fadilah (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2023)
ABSTRACTThis study endeavors to reinvigorate the concept of critical digital literacy within the framework of English language teaching in Indonesia. Employing a desk study methodology, a nexus analysis was conducted, encompassing theoretical frameworks, empirical research, political-ideological considerations, governmental and global institutional policies, and pedagogical possibilities related to the integration of critical digital literacy with digital technology in education. The data analysis involves the systematic deconstruction and synthesis of existing literature frameworks to establish emergent categories. These categories were subsequently thematized into a model, serving as a heuristic framework that spans the multifaceted domains of digital text, digital reader, digital task, and digital values. The framework underscores the imperative to prioritize human transformation and empowerment over a sole focus on digital technology utilization. It emphasizes the collaborative efforts required among stakeholders in English language teaching practices.ABSTRAKPenelitian ini berupaya untuk menyegarkan kembali konsep literasi digital kritis dalam kerangka pengajaran bahasa Inggris di Indonesia. Dengan menerapkan metodologi desk study, analisis nexus diterapkan dengan menggabungkan kerangka teoritis, penelitian empiris, pertimbangan politik-ideologis, kebijakan pemerintah dan lembaga global, serta peluang-peluang pedagogis terkait integrasi literasi digital kritis dengan teknologi digital dalam pendidikan. Analisis data melibatkan dekonstruksi sistematis dan sintesis terkait dengan kerangka literatur yang ada untuk membentuk kategori-kategori yang muncul. Dari kategori-kategori tersebut kemudian di bentuk menjadi tema yang kemudian dikembangkan sebuah model yang berfungsi sebagai kerangka heuristik yang mencakup domain-domain beraneka bentuk, seperti teks digital, pembaca digital, tugas digital, dan nilai-nilai digital. Kerangka ini menekankan pentingnya untuk memberikan prioritas pada transformasi dan pemberdayaan manusia dibandingkan dengan fokus semata-mata pada pemanfaatan teknologi digital. Penekanan diberikan pada upaya kolaboratif yang diperlukan di antara para pemangku kepentingan dalam praktik pengajaran bahasa Inggris.How to Cite: Fadilah, E. (2023). A Multifaceted Framework for Critical Digital literacy in Transforming Human Resources. IJEE (Indonesian Journal of English Education), 10(2), 463-486. doi:10.15408/ijee.v10i2.32036.